The relationship between trade openness and industrialization in Central Africa - (:unkn) unknown (My University, 2021)
Since independence in the 1960s, Central African countries have recorded poor performance in the manufacturing industry. Several industrial strategies were experimented with, in particular import substitution in the 1960s and 1970s, and macroeconomic stabilization reforms in the 1980s and 1990s to improve the international competitiveness of Central African firms.With the application of the reforms, the countries of Central Africa have chosen trade openness. Thus, the objectives of this research were to understand and explain the effects of trade openness on industrialization in Central Africa. Because, industrialization has a preponderant role in the economic development of nations. Very few countries have reached the stage of developed countries without an efficient industrial base. The low level of development of the manufacturing industry in Central Africa does not offer enough job opportunities to the working population, which is growing in number, resulting in an increase in its level of poverty.The research concerned the 11 members countries of the Economic Community of Central African States (ECCAS). To conduct this research, we used the basic theoretical model of Lucas (1988), in order to highlight the empirical link between trade openness and the performance of the manufacturing industry. We used panel data regressions with the fixed effects estimation method.At the end of the research, we found a positive effect of trade openness on the performance of the manufacturing industry. Indeed, the 1% increase in trade as a percentage of GDP leads to a 2.3% increase in the value added of manufacturing industry as a percentage of GDP. Similarly, the impact of an additional year of schooling results in an 8% increase in the added value of manufacturing industry as a percentage of GDP. Finally, increasing the proportion of the active population in the population by 1% makes it possible to improve the added value of the manufacturing industry by around
Keywords: African Research